2018
DOI: 10.1155/2018/6260458
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Spectroscopic and Structural Analysis of TiO2/WO3 Composite Semiconductors

Abstract: WO3-TiO2 composite materials were obtained using commercial titania (Evonik Aeroxide P25) and hydrothermally crystallized WO3. Different ratios of TiO2/WO3 were investigated, starting at 1 wt.% of WO3 to 50 wt.%. The morphology of WO3 was of the star-like type, and its structure is basically composed of monoclinic crystalline phase. All spectroscopic characteristics of the composites and their derived data (band-gap energy value, light absorption threshold, and IR specific bands) directly varied with the incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The analysis of IR spectra revealed the presence of specific signals of TiO 2 and WO 3 without any major changing trend. The peak in the 400–410 cm −1 range was due to stretching vibrations of Ti−O and TivO−Ti [57,58] . The main peak near 1000–1100 cm −1 in all the samples was related to different W−O−W stretching vibrations, particularly W=O bonds near 1060 cm −1 [59] .…”
Section: Resultsmentioning
confidence: 88%
“…The analysis of IR spectra revealed the presence of specific signals of TiO 2 and WO 3 without any major changing trend. The peak in the 400–410 cm −1 range was due to stretching vibrations of Ti−O and TivO−Ti [57,58] . The main peak near 1000–1100 cm −1 in all the samples was related to different W−O−W stretching vibrations, particularly W=O bonds near 1060 cm −1 [59] .…”
Section: Resultsmentioning
confidence: 88%
“…As only AW10 nm contains 6% WO 3 , to minimize the size influence and to keep a percentage of WO 3 , 40% of AW10 nm was used to make a WO 3 content of 2.4%. In the literature, after a comparison of WO 3 addition from 1%‐50%, it was found that 24% WO 3 content in a TiO 2 /WO 3 composite contributed the best photocatalytic activity in oxalic acid degradation …”
Section: Methodsmentioning
confidence: 99%
“…The answer lies mainly in the previously mentioned energetic criteria. Coupling of WO 3 with TiO 2 -in a well-determined ratio, using the corresponding method of preparation -either physical mixing [18] or pH adjustment corresponding to the surface charge of the components of the composite [19] is considered as an efficient way to prepare composites with great sensorial and photocatalytic efficiency (in certain cases, such as phenol, methyl-orange) [20][21]. According to Lee and coworkers, the excitation of TiO 2 /WO 3 composites triggers the following steps [22]: (i) the excitation of semiconductors and the formation of charge carriers, (ii) charge-transfer (WO 3 (h + , e -) / TiO 2 (h + , e -) → WO 3 (e -) / TiO 2 (h + )), (iii) re-oxidation of W 5+ to W 6+ due to the involvement of molecular O 2 .…”
Section: Introductionmentioning
confidence: 99%